PERUBAHAN KARAKTERISTIK SIFAT KIMIA TANAH PADA AREAL PENGEMBANGAN PENELITIAN LAHAN KERING GLE GAPUI - Karnilawati Karnilawati; Cut Mulia Sari; Musfirah Musfirah (Jurnal Sains Riset, 2022)
Dry land is one of the that has the characteristic of the chemical properties of the soil that is less fertile, so that it can reduce the potential for agricultural development. Low soil fertility is an abstacle in the development of dry land. This study aims to determine changes in the chemical characteristics of the Gle Gapui dry land research development area from 2016 to 2020. This research was carried out at the Experimental Gardening of the Faculty of Agriculture, Jabal Ghafur University. The method used in this study was descriptive-quantitative method by analyzing several parameters of soil chemical properties, namely soil pH, C-organic, N-total, available P, Ca-dd, Mg-dd, K-dd, Al-dd, Kb and DHL. The results of the study indicate that there has been a change in the characteristics of the chemical properties of the soil at SPL 4 in the Gle Gapui dry land research development area.Keywords: characteristic, chemical properties, dry land